Stress-path Dependency of Resilient Behaviour of Granular Materials - Liu, Ying (My University, 2010)
The resilient modulus and Poisson's ratio of granular materials used in flexible pavement structures is highly nonlinear, stress/strain path and direction-dependent. Resilient properties are very important for realistic flexible pavement design. By far, several important aspects, such as the effect of stress path, major principal stress rotation, initial stress state and inherent fabric, on the cross-anisotropic resilient properties are not fully understood. The main objective of this thesis was to study the cross-anisotropic resilient properties of granular materials along various stress paths from both initial isotropic and initial anisotropic stress states. Extensive resilient modulus stress path tests were performed for this purpose.
In this research, the resilient behaviour of the test material for initial isotropic stress states along various stress paths was investigated first, with particular interest in the stress/strain path dependency. New resilient modulus equations were then developed, by taking into account the effect of confining pressure and resilient strains. These equations can be used to estimate the cross-anisotropic resilient modulus corresponding to initial isotropic stress states. Selection of Poisson's ratio was also investigated.
The effect of initial stress state on the resilient responses was studied through a series of stress path tests with constant confining pressure and constant vertical stress, respectively. Based on the experimental findings, revised equations for resilient modulus and Poisson's ratio were proposed to account for the effect of ratio of initial horizontal stress to vertical stress (Kini). The proposed equations can predict the cross-anisotropic resilient properties for various stress paths corresponding to initial isotropic/anisotropic stress conditions.
In order to provide a more comprehensive insight into the complex resilient properties of granular materials along different stress/strain paths for various initial stress states, a micromechanics approach was introduced to back-calculate the degree of fabric anisotropy. The variations of fabric with stress path, initial stress state and final stress state (i.e., state which corresponds to the peak stress during cyclic loading) were investigated. To provide a reliable prediction of initial/inherent fabric anisotropy and fabric evolution in constitutive s with embedded microstructure, an evolution law of fabric anisotropy was developed.
Keywords: granular materials; isotropic stress; anisotropic stress; resilient behaviour